Strategy for Religious Character Development for MTs Nuril Huda Tarub Tawangharjo Grobogan Students in Facing Era 4.0 - Yulianto, Ghufron Hamzah (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
ABSTRACTMts Nuril Huda Tarub Student Religious Character Development Strategy Tawangharjo Grobogan in Facing Era 4.0. Semarang: Masters Program in Islamic Religious Education, Wahid Hasyim University Semarang. The year 2020 is to use the integration and supplement model, this integration model is to integrate the development of religious character in all subjects and be able to provide good examples for students. The second model, which is a supplement model of this model, the implementation of religious character development through an activity outside school hours can be reached through an extracurricular activityKeywords: Era 4.0, Religion, Learning Strategy